Pengembangan Mathematics Olympiad Digital Book (MODiB) Berdasarkan Strategi Pemecahan Masalah Polya untuk Meningkatkan Kreativitas dan Hasil Belajar Matematika Siswa Sekolah Dasar - Krisetiawan, Krisetiawan; Buchori, Achmad; Handayani, Arri (Universitas PGRI Semarang, 2023)
Mathematics Olympiad is a prestigious competition that is growing and has many enthusiasts in Indonesia. Thus the need for math olympiad teaching media is getting higher. The purpose of this research is to develop a digital book that is 1) valid, 2) practical and 3) effective for improving learning outcomes and mathematical creativity of elementary school students, which is named MODiB (Mathematics Olympiad Digital Book). MODiB contains Elementary Mathematics Olympiad material according to the OSN syllabus and in solving problems using the Polya Problem Solving Strategy. MODiB development applies the 5 steps of ADDIE (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were SD DCS Semarang students who had passed the selection for OSN guidance. Starting with analyzing the condition of coaching mathematics Olympiads at SD DCS Semarang and recording the needs needed to foster the OSN team, designing and developing MODiB accompanied by validators who are material experts and media experts, and then implementing MODiB at SD DCS Semarang. Evaluation is carried out at each stage and after implementation is complete. From the research results, data were obtained: 1) the feasibility results of the material on MODiB were 89.09% which were included in the feasible category to be tested on students, and the feasibility results of learning media were 88.57% in the feasible category to be tested on students, 2) practical results MODiB according to students is 80.48% which is included in the practical category, 3) the results of the analysis of increasing learning outcomes with the gain test obtained a score 0,244 that is included in the low category based on the Gain score category according to Hake, and 4) the value of mathematical creativity of 16 respondents (53.3 %) increased, 4 respondents (13.3%) remained and 10 respondents (33.3%) decreased. Overall, the average increase in the value of mathematical.